The Goths & Other Stories Second Edition - Zamler-Carhart, Tis Kaoru (punctum books, 2023)
In the winter of 476 AD, the Ostrogoths, hungry and exhausted from wandering for months along the barren confines of the Byzantine Empire, write to Emperor Zeno in Constantinople, requesting permission to enter the walled city of Epidaurum and just kinda crash and charge their phones. Closer to home, Orpheus drags behind him a marble-still Eurydice through a refrigerator. The poetics of car accidents, capitalist consumption, and anarchist terrorism unfold at a Southern California car dealership. The winged messenger Mercury shows up in the apartment of a tax accountant to announce that "hell is coming to town." Rebels attempt to overthrow the president of Burkina Faso with rotten snails. In The Goths & Other Stories, sexual desire, food, space, and anger are contorted. Prose fiction, experimental poetry, drama, letters, philosophy, and design theory intersect and breed. Readers of all centuries will feel at home in this book. The smell of seafood and speculative urban planning merge into a 1990s computer game, Abidjan has 12,756 streets with no way to go from one to another, and an apocalypse of tax law and classical mythology descends upon suburbia and reveals a medieval theology of design, theater, and light. The book's six stories are set in different times and places - sometimes within the same narrative - but have in common a slippery approach to the boundaries between fiction and theory, between ontological planes, and between the comical and the moral. Together they form a treatise on the nature of writing as a branch of design - one whose medium is easier to reveal than to define.